ANALISIS PENGARUH MEDIA PEMBELAJARAN TERHADAP MINAT BELAJAR SISWA MI DI TANJUNG PURA - Husnah, Diah Hafizhotul (STKIP Paris Barantai, 2024)
This research aims to describe the influence of the use of learning media on student interest and learning outcomes at MI Tanjung Pura. This research is field research using a quantitative approach with survey research methods. The research population was 174 students and the sample in this study was 63 students from grades 1 to 6 at MI Tanjung Pura. The data collection methods used are questionnaires and documentation. The data analysis technique used is simple linear regression analysis. The results of this research show that there is a significant influence of the media and students' interest in learning on the learning outcomes of students in grades 1 to 6 at MI Tanjung Pura. The magnitude of the influence of media and interest in learning on student learning outcomes is 0.699, which means that media and interest in learning influence learning outcomes by 69.9%, while the remainder is influenced by other factors not discussed in the research